PENGARUH KETERLIBATAN PELANGGAN DAN KUALITAS PELAYANAN TERHADAP PERTUMBUHAN PENJUALAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI PADA DAPURMAMIASRI - Iswara Aristia; Yadhurani Dewi Amritha (Journal of Innovative and Creativity, 2026)
his study aims to analyze the influence of customer engagement and service quality on sales growth mediated by customer satisfaction at DapurMamiAsri, a culinary business located in Sanur, Bali. The intense competition within the culinary sector, particularly in the tourism area of Denpasar, highlights the need for businesses to strengthen customer relationships and service strategies to sustain growth. This quantitative research involved 150 customers selected using Slovin’s formula through simple random sampling. Data were collected using a five-point Likert-scale questionnaire and analyzed with Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings show that customer engagement and service quality significantly and positively influence customer satisfaction. Customer satisfaction further enhances sales growth and mediates the relationship between customer engagement and service quality with sales growth. This research supports Relationship Marketing Theory by emphasizing the strategic role of engagement and service quality in developing customer satisfaction and driving business performance. Practically, the findings offer insights for culinary businesses to improve customer experience and strengthen competitive advantage.